LOGICAL FRAMEWORK MATRIX (LFM) IN MALAYSIA GOVERNMENT PROJECT PLANNING - Zakaria, Norhanim; Muhamed Yusuff, Nurul Izzati; Ali, Azlan Shah; Zolkafli, Umi Kalsum (Journal of Surveying, Construction and Property, 2020)
The Malaysian Government adopted the Logical Framework Approach (LFA) as a crucial project management tool in implementing Outcome Based Approach (OBA) for public projects in 2009 via the issuance of the Guideline for Planning and Preparation of Programs and Projects Development 1/2009. The guideline was issued by the Economic Planning Unit (EPU) of the Prime Minister’s Department (JPM) (also known as Ministry of Economic Affairs (MEA) since 2018), Malaysia. The Logical Framework Matrix (LFM) has been suggested as a key tool for project appraisal. However, there are some cases where the LFM has not been appropriately utilized by the ministries and agencies. This paper therefore presents the frequent failings of LFM and practical issues in the participatory approach of LFA process, which contribute to the LFM produced. Findings from the study conducted via document review and interview confirmed that frequent failings of LFM and practical issues occur in preparing LFM in Malaysia Government project planning. Three (3) measures to overcome the existing challenges as well as in reducing existing gaps were identified to include knowledge management, enforcement and format.